Care work in the context of austerity. (June 2015) - Baines, Donna; Cunningham, Ian
This introduction establishes the context for a series of articles exploring the outcomes for work, employment, worker orientation and service quality from the emerging context of austerity in public services in three countries – Canada, the UK and Australia. The paper outlines the development of outsourcing in care under new public management and identifies broad trends in work and employment pre-austerity. It reveals contracting-out and new public management-diminished public provision, radically altering the non-profit sector. The financial crisis is the latest in successive rounds of market-based reform that are deepening these tendencies. Despite some national variations, new public management led to the pay of the predominantly female front line workforce across the three countries failing to keep pace with public sector counterparts, as well as cuts in pensions, sick pay, and travel and subsistence allowances. Finally, it outlines how the accompanying papers explore new facets and themes in care work during austerity.